A quinoline derivative and an organic electroluminescent device containing the same

By using quinoline derivatives to form a stable six-membered chelate with metal ions and introducing conjugated rigid heteroaryl structures, the problems of poor transport performance of charge generation layer materials and doped metal diffusion in OLED devices are solved, achieving more efficient charge transport and longer service life.

CN119039323BActive Publication Date: 2025-03-18SHIJIAZHUANG CHENGZHI YONGHUA DISPLAY MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411533422.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-18
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

In existing OLED devices, the transmission performance of the charge-generating layer material is poor, resulting in limited performance of the stacked device, and the diffusion of doped metal leads to material deterioration and shortened lifetime.

Method used

The quinoline derivative is used to form a stable six-membered chelate with metal ions, which improves the stability and transport performance of the charge generation layer, and optimizes the molecular structure to improve mobility by introducing a conjugated rigid heteroaryl structure.

Benefits of technology

It improves charge generation ability and injection performance, reduces driving voltage, improves luminous efficiency and service life, and avoids material deterioration caused by metal ions diffusion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119039323B_ABST
    Figure CN119039323B_ABST
Patent Text Reader

Abstract

The present invention discloses a quinoline derivative and an organic electroluminescent device comprising the same. The general structural formula of the quinoline derivative is shown in Formula I, wherein Ar1-Ar 10 Each independently represents hydrogen, deuterium or a group shown in formula II, and at least one represents a group shown in formula II. By utilizing the six-membered stable chelate ring formed by the quinoline skeleton, on the one hand, the stability of the complex can be improved, the doping effect can be enhanced, and the electron injection ability can be improved. On the other hand, after the stability of the complex is improved, it is more difficult for metal ions to diffuse, avoiding the material degradation and life reduction caused by the diffusion of metal ions to the hole end. The substitutable conjugated rigid heteroaryl structure introduced into the structure of the quinoline derivative of the present invention makes the material have a smaller electronic reorganization energy, which is beneficial to improve the mobility, so that the electrons in the charge generation layer can be quickly transmitted to the adjacent layer, thereby improving the device efficiency. #imgabs0#I;#imgabs1#II.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of OLED, and specifically comprises a quinoline derivative and an organic electroluminescent device comprising the same. Background Art

[0002] An OLED device formed by connecting multiple OLED light-emitting units in series is called a stacked OLED device. In a stacked OLED device, two independent light-emitting units are connected in series through a charge generation layer (CGL), and the charge generation layer is usually constructed in the form of a pn structure. In order to improve the charge generation and injection capabilities, the charge generation layer often adopts a doping method, where the doping material in the hole generation layer is p-doped, such as F4-TCNQ, and the doping material in the electron generation layer is n-doped, usually a metal with a low work function, such as Li, Mg, Yb, etc. The n-doped material can form a complex with the CGL material, and this complex can greatly affect the performance of the stacked device. Traditional n-doping uses alkali metal materials with a small radius such as Li. Due to the strong diffusion ability of alkali metals, when the alkali metal diffuses into the hole of the charge generation layer Ends will lead to severe material degradation, rapidly reducing the efficiency and life of the device. Subsequently, the stability of the complex is improved by introducing organic materials with multi-dentate ligands to form chelates with doped metals, such as phenanthroline, bipyridine and other fragments. The aromatic ligands on most chelates form a five-membered ring with the metal. For most aromatic ligands, due to the presence of conjugated double bonds and conjugated π bonds, the atoms on the ring are mostly SP2 hybridized, and the corresponding theoretical bond angle is 120°, while the bond angle of the five-membered ring is 108°. According to the Bayer tension theory, each bond needs to bend inward (120°-108°) / 2=6°, so there is a certain ring tension, which makes it impossible to further improve the stability of the chelate.

[0003] At the same time, in some stacked devices, the electrons formed in the charge generation layer are transferred from the pn interface to the electron transport layer or the light-emitting layer. Therefore, the transport performance of the charge generation layer also has an important influence on the stacked device. Different from common electron transport materials (ET materials), ET materials usually introduce strong electron-pulling groups such as triazine and pyridine to increase the material's affinity for electrons to enhance the electron transport properties. However, for the charge generation layer materials, strong electron-pulling fragments will weaken the coordination ability of the coordination group, which makes the transport performance of the charge generation layer materials poor, which restricts the commercialization process of stacked devices to a certain extent.

[0004] Therefore, it is very necessary to develop new charge generation layer materials with small bending angle, small electron reorganization energy and high mobility to improve the performance of organic light-emitting devices. Summary of the invention

[0005] In view of the above problems existing in the prior art, the present invention provides a quinoline derivative and an organic electroluminescent device comprising the same.

[0006] To achieve the above objectives, the technical solutions adopted by the present invention include:

[0007] The first aspect of the present invention provides a quinoline derivative, the general structural formula of the quinoline derivative is shown in Formula I;

[0008] I; II;

[0009] Among them, Ar1-Ar 10 Each independently represents hydrogen, deuterium or a group represented by formula II, and at least one represents a group represented by formula II;

[0010] In Formula II, L represents any one of a single bond and an arylene group having carbon atoms of C6-C18;

[0011] X represents O or S;

[0012] Y1 and Y2 each independently represent C or N;

[0013] Ring A and Ring B each independently represent a benzene ring that can be connected in parallel with the structure of Formula II;

[0014] Ar 11 represents an aromatic group having carbon atoms of C6-C18;

[0015] In formula I and formula II, any hydrogen can be replaced by deuterium, and any nitrogen can be replaced by 15 N substitution, any sulfur can be 33 S. 34 S or 36 S is substituted, any oxygen can be 17 O or 18 O substitution, any carbon can be 13 C substituted.

[0016] The present invention uses a quinoline derivative, which can form a stable six-membered chelate with metal ions of various radius sizes. According to the Bayer tension theory, the six-membered ring containing an unsaturated bond has less tension than a five-membered ring and is more stable. The quinoline has a planar structure and less steric hindrance, which is conducive to using multiple organic fragments of the present invention and metals to form multiple chelate rings through a chelate effect, further increasing the stability of the complex, and is conducive to doping metals and organic materials to form a stable charge generation layer, thereby improving the charge generation ability and injection performance, thereby reducing the driving voltage of the stacked device; the quinoline fragment and the diaryl furan fragment are connected through L, and the π electrons on the diaryl furan with a larger conjugated surface can adjust the coordination ability of the quinoline part through the conjugation effect, and heteroatoms can be introduced into the diaryl furan fragment to adjust its electron-rich characteristics. The quinoline fragment and the diaryl furan fragment are directly connected or connected through a rigid aryl fragment, so that the overall rigidity of the molecular structure is better, the reorganization energy is smaller, and the mobility is larger, thereby further improving the driving voltage.

[0017] Furthermore, Ar1, Ar3, Ar5, Ar6, Ar8, Ar 10 At least one of them is represented by the group shown in formula II.

[0018] Furthermore, the formula II is selected from one of the structures shown below:

[0019] .

[0020] Furthermore, the formula I is selected from one of the structures shown below:

[0021] , , .

[0022] Furthermore, L represents any one of a single bond and a phenylene group.

[0023] Furthermore, X represents O.

[0024] Furthermore, Ar 11 Represents pyrene.

[0025] Furthermore, the quinoline derivative is selected from one of the structures shown below:

[0026]

[0027]

[0028]

[0029]

[0030]

[0031]

[0032]

[0033]

[0034]

[0035]

[0036]

[0037]

[0038]

[0039]

[0040]

[0041]

[0042]

[0043]

[0044]

[0045]

[0046]

[0047]

[0048]

[0049]

[0050]

[0051]

[0052]

[0053]

[0054]

[0055]

[0056]

[0057]

[0058]

[0059]

[0060]

[0061]

[0062]

[0063]

[0064]

[0065]

[0066]

[0067]

[0068]

[0069]

[0070]

[0071]

[0072]

[0073]

[0074]

[0075]

[0076]

[0077]

[0078]

[0079]

[0080]

[0081]

[0082]

[0083]

[0084]

[0085]

[0086]

[0087]

[0088]

[0089]

[0090]

[0091]

[0092]

[0093]

[0094]

[0095]

[0096]

[0097]

[0098]

[0099]

[0100]

[0101] .

[0102] The second aspect of the present invention provides an organic electroluminescent device, comprising an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer, which are sequentially arranged on a substrate; wherein the charge generation region includes one or more of the above-mentioned quinoline derivatives.

[0103] Furthermore, the charge generation region includes an n-type charge generation layer and a p-type charge generation layer, wherein the n-type charge generation layer includes one or more quinoline derivatives as described above.

[0104] Beneficial effects of the present invention:

[0105] The present invention uses a quinoline derivative, which can form a stable six-membered chelate with metal ions of various radius sizes. According to the Bayer strain theory, the six-membered ring containing an unsaturated bond has less strain than a five-membered ring and is more stable. The quinoline is a planar structure with less steric hindrance, which is conducive to multiple organic fragments of the present invention and metals forming multiple chelate rings through a chelate effect, further increasing the stability of the complex, and is conducive to the formation of a stable charge generation layer by doping metals and organic materials, thereby improving the charge generation ability and injection performance, thereby reducing the driving voltage of the stacked device; the quinoline fragment and the diaryl furan fragment are connected through L, and the π electrons on the diaryl furan with a larger conjugated surface can adjust the coordination ability of the quinoline part through the conjugation effect, and heteroatoms can be introduced into the diaryl furan fragment to adjust its electron-rich characteristics. The quinoline fragment and the diaryl furan fragment are directly connected or connected through a rigid aryl fragment, so that the overall rigidity of the molecular structure is better, the reorganization energy is smaller, and the mobility is larger, thereby facilitating further improvement of the driving voltage. Simultaneously, the rigid heteroaryl of larger conjugated surface is introduced and mostly asymmetric structure is presented, with less bending angle and less electronic reorganization energy, the fragment of planar rigidity is also conducive to molecular stacking, is conducive to the increase of mobility, makes the electron in charge generation layer can be transmitted to adjacent layer faster, therefore the device prepared by material of the present invention has good device performance. In addition, after the coordination complex stability is improved, makes metal ion more difficult to diffuse, avoids the material degradation and life reduction that metal ion diffuses to hole end and causes. Therefore, the organic electroluminescent device prepared by utilizing quinoline derivative of the present invention has lower driving voltage, higher luminous efficiency and longer service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0106] Figure 1 It is a schematic structural diagram of the organic electroluminescent device of the present invention. DETAILED DESCRIPTION

[0107] In order to more clearly understand the content of the present invention, it will be described in detail with reference to the drawings and embodiments.

[0108] The quinoline derivatives of the present invention are suitable for use in light-emitting elements, display panels and electronic devices, and are particularly suitable for use in organic electroluminescent devices. The electronic device of the present invention is a device comprising a layer of at least one organic compound, and the device may also comprise an inorganic material or a layer formed entirely of an inorganic material. The electronic device is preferably an organic electroluminescent device (OLED). The schematic structural diagram of an exemplary organic electroluminescent device is shown in FIG. Figure 1 shown.

[0109] Experimental Section

[0110] In order to understand the content of the present invention more clearly, the luminescent characteristics of the described quinoline derivatives, the preparation method of the described quinoline derivatives and the described device will be explained in detail in conjunction with the examples. Various chemical reactions can be applied to the synthetic method of the compound of an embodiment of the present invention. But it should be noted that the synthetic method of the compound of an embodiment of the present invention is not limited to the synthetic method described below. Unless otherwise indicated, the subsequent synthesis is carried out in anhydrous solvent under a protective gas atmosphere. Solvents and reagents can be purchased from conventional reagent suppliers.

[0111] Intermediate Synthesis Example 1

[0112]

[0113] Under nitrogen protection, D1 (2.60 g, 10.5 mmol), E1 (4.10 g, 10 mmol), potassium carbonate (2.76 g, 20 mmol), triphenylphosphine (0.26 g, 1 mmol), Pd(OAc)2 (0.12 g, 0.5 mmol) were added to the reaction bottle, and a mixture of deoxygenated solvents acetonitrile and methanol (50 mL of acetonitrile and 25 mL of methanol) was added, and the reaction was carried out at 60°C for 24 hours. After the reaction, the reaction system was cooled to room temperature, filtered, and the filtrate was collected. After the filtrate was desolvated, it was dissolved in 50 mL of dichloromethane, 50 mL of water was added, stirred for 5 minutes, and then separated. This was repeated twice. The organic phase was finally desolvated by a rotary evaporator, and then purified by column chromatography on silica (hexane: ethyl acetate = 30:1, v / v), and the product F1: 3.70 g (yield: 90%) was finally obtained, MS (m / z) (M+): 411.

[0114] Under nitrogen protection, F1 (4.11 g, 10 mmol), trimethylsilyl acetylene (1.18 g, 12 mmol), bistriphenylphosphine palladium dichloride (0.35 g, 0.5 mmol), CuI (0.10 g, 0.5 mmol), and 25 mL of diisopropylamine were added to the reaction bottle, and the reaction was carried out at 80°C for 4 hours. After the reaction, the reaction system was cooled to room temperature, filtered, and the filtrate was collected. After the solvent was removed from the filtrate, it was purified by column chromatography on silica (hexane: ethyl acetate = 20:1, v / v), and the product G1 was finally obtained: 3.09 g (yield: 81%), MS (m / z) (M+): 381.

[0115] Under nitrogen protection, G1 (3.81 g, 10 mmol), potassium carbonate (1.38 g, 10 mmol), and a mixture of methanol and dichloromethane (20 mL methanol and 10 mL dichloromethane) were added to the reaction flask, and the mixture was reacted at 25°C for 0.5 h. The mixture was filtered, the filtrate was collected, the solvent was removed by rotary evaporation, 50 mL dichloromethane was used to dissolve the filtrate, 50 mL water was added, and the mixture was separated after stirring for 5 min. This was repeated twice. The organic phase was finally freed of the solvent using a rotary evaporator, and then purified by column chromatography on silica (hexane: ethyl acetate = 15:1, v / v), and the product H1 was finally obtained: 2.63 g (yield: 85%), MS (m / z) (M+): 309.

[0116] Under nitrogen protection, H1 (3.09 g, 10 mmol), platinum dichloride (0.27 g, 1 mmol), and 25 mL of chlorobenzene were added to the reaction bottle, and the reaction was carried out at 130°C for 20 h. The filtrate was filtered and collected. After the solvent was removed from the filtrate, it was purified by recrystallization from toluene, and finally the product A1 was obtained: 1.85 g (yield: 60%), MS (m / z) (M+): 309.

[0117] Other type A intermediates can be prepared by referring to the above method and selecting raw materials with different substitution positions, which will not be listed here one by one.

[0118] Intermediate Synthesis Example 2

[0119]

[0120] Compound J-1 (22.10 g, 100 mmol), K-1 (25.30 g, 100 mmol), tetrakis(triphenylphosphine)palladium (1.16 g, 1.00 mmol), tetrabutylammonium bromide (3.22 g, 1.00 mmol), potassium carbonate (20.70 g, 150 mmol), 250 mL of toluene, 125 mL of ethanol, and 100 mL of deionized water were added to a dried round-bottom flask replaced with nitrogen. The temperature was raised to 78 ° C. under stirring and maintained for 8 h. The reaction mixture was then cooled to room temperature, 200 mL of deionized water was added, stirred for 15 min, the organic phase was separated, the organic phase was dried over anhydrous magnesium sulfate, and the solvent was removed under reduced pressure to obtain a crude product. The crude product was purified by silica gel column chromatography (dichloromethane / n-heptane as the mobile phase) to obtain intermediate L-1: 21.21 g, yield: 70%, MS (m / z) (M+): 303.

[0121] To a dried and nitrogen-substituted round-bottom flask, add intermediate L-1 (27.27 g, 90 mmol), potassium carbonate (37.26 g, 270 mmol), and 300 mL of N-methylpyrrolidone. Stir at 160 °C for 2 h under nitrogen protection. Remove the solvent under reduced pressure to obtain a crude product. Wash the crude product with deionized water and ethanol, dry it, and purify it with silica gel column chromatography (dichloromethane / n-heptane as the mobile phase) to obtain intermediate M-1: 17.20 g, yield: 68%, MS (m / z) (M+): 283.

[0122] Compound M-1 (2.83 g, 10 mmol), pyreneboric acid (2.46 g, 10 mmol), tetrakis(triphenylphosphine)palladium (0.12 g, 0.10 mmol), tetrabutylammonium bromide (0.32 g, 0.10 mmol), potassium carbonate (2.07 g, 15 mmol), 25 mL of toluene, 12.5 mL of ethanol, and 10 mL of deionized water were added to a dried round-bottom flask replaced with nitrogen. The temperature was raised to 78 ° C. under stirring and maintained for 8 h; then the reaction mixture was cooled to room temperature, 20 mL of deionized water was added, stirred for 15 min, the organic phase was separated, the organic phase was dried over anhydrous magnesium sulfate, and the solvent was removed under reduced pressure to obtain a crude product; the crude product was purified by silica gel column chromatography (dichloromethane / n-heptane as mobile phase) to obtain intermediate N-1: 3.72 g, yield: 92%, MS (m / z) (M+): 404.

[0123] Under nitrogen protection, N-1 (4.04 g, 10 mmol), p-diphenylboronic acid (1.66 g, 10 mmol), potassium carbonate (4.14 g, 30 mmol), tetrakis(triphenylphosphine)palladium (0.12 g, 0.1 mmol) were added to the reaction flask, and a mixture of deoxygenated solvent tetrahydrofuran and water (80 mL of tetrahydrofuran and 20 mL of water) was added, and the reaction was carried out at 60°C for 12 hours. After the reaction was completed, the reaction system was cooled to room temperature, 60 mL of water was added, stirred for 5 minutes, and then separated. The organic phase was washed with 120 mL of water again and separated, and the reaction was repeated twice. The organic phase was finally freed of solvent using a rotary evaporator, and the obtained solid was recrystallized and purified using toluene to finally obtain the product B1: 3.91 g (yield: 80%), MS (m / z) (M+): 489.

[0124] Other type B intermediates can be prepared by referring to the above method and selecting different raw materials, which will not be listed here one by one.

[0125] Synthesis Example 1

[0126]

[0127] Under nitrogen protection, A1 (3.09 g, 10 mmol), B1 (4.89 g, 10 mmol), potassium carbonate (4.14 g, 30 mmol), tetrakis(triphenylphosphine)palladium (0.12 g, 0.1 mmol) were added to the reaction flask, and a mixture of deoxygenated solvent tetrahydrofuran and water (80 mL of tetrahydrofuran and 20 mL of water) was added, and the reaction was carried out at 60°C for 12 hours. After the reaction was completed, the reaction system was cooled to room temperature, 60 mL of water was added, stirred for 5 minutes, and then separated. The organic phase was washed with 120 mL of water again and separated, and the reaction was repeated twice. The organic phase was finally freed of solvent using a rotary evaporator, and the obtained solid was recrystallized and purified using toluene to finally obtain the product C1: 6.13 g (yield: 91%), MS (m / z) (M+): 674.

[0128] Synthesis Example 2

[0129]

[0130] The method is the same as that of Synthesis Example 1, except that A2 (3.09 g; 10 mmol) and B2 (4.89 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C2: 5.52 g (yield: 82%), MS (m / z) (M+): 674.

[0131] Synthesis Example 3

[0132]

[0133] The method is the same as that of Synthesis Example 1, except that A3 (3.09 g; 10 mmol) and B3 (4.13 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C3: 5.44 g (yield: 91%), MS (m / z) (M+): 598.

[0134] Synthesis Example 4

[0135]

[0136] The method is the same as that of Synthesis Example 1, except that A4 (3.09 g; 10 mmol) and B4 (4.13 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C4: 5.14 g (yield: 86%), MS (m / z) (M+): 598.

[0137] Synthesis Example 5

[0138]

[0139] The method is the same as that of Synthesis Example 1, except that A5 (3.09 g; 10 mmol) and B5 (4.13 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C5: 5.56 g (yield: 93%), MS (m / z) (M+): 598.

[0140] Synthesis Example 6

[0141]

[0142] The method is the same as that of Synthesis Example 1, except that A6 (3.09 g; 10 mmol) and B6 (4.13 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C6: 5.14 g (yield: 86%), MS (m / z) (M+): 598.

[0143] Synthesis Example 7

[0144]

[0145] The method is the same as that of Synthesis Example 1, except that A7 (3.09 g; 10 mmol) and B7 (4.63 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C7: 6.16 g (yield: 95%), MS (m / z) (M+): 648.

[0146] Synthesis Example 8

[0147]

[0148] The method is the same as that of Synthesis Example 1, except that A8 (3.09 g; 10 mmol) and B8 (4.63 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C8: 5.31 g (yield: 82%), MS (m / z) (M+): 648.

[0149] Synthesis Example 9

[0150]

[0151] The method is the same as that of Synthesis Example 1, except that A9 (3.09 g; 10 mmol) and B9 (4.63 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C9: 5.64 g (yield: 87%), MS (m / z) (M+): 648.

[0152] Synthesis Example 10

[0153]

[0154] The method is the same as that of Synthesis Example 1, except that A10 (3.09 g; 10 mmol) and B10 (4.13 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C10: 5.50 g (yield: 92%), MS (m / z) (M+): 598.

[0155] Synthesis Example 11

[0156]

[0157] The method is the same as that of Synthesis Example 1, except that A11 (3.09 g; 10 mmol) and B11 (4.13 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C11: 4.90 g (yield: 82%), MS (m / z) (M+): 598.

[0158] Synthesis Example 12

[0159]

[0160] The method is the same as that of Synthesis Example 1, except that A12 (3.09 g; 10 mmol) and B12 (4.63 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C12: 5.31 g (yield: 82%), MS (m / z) (M+): 648.

[0161] Synthesis Example 13

[0162]

[0163] The method is the same as that of Synthesis Example 1, except that A13 (3.09 g; 10 mmol) and B13 (4.63 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C13: 5.89 g (yield: 91%), MS (m / z) (M+): 648.

[0164] Synthesis Example 14

[0165]

[0166] The method is the same as that of Synthesis Example 1, except that A14 (3.09 g; 10 mmol) and B14 (4.62 g; 10 mmol) are used to replace A1 and B1, respectively, to obtain the product C14: 5.76 g (yield: 89%), MS (m / z) (M+): 647.

[0167] Synthesis Example 15

[0168]

[0169] The method is the same as that of Synthesis Example 1, except that A15 (3.09 g; 10 mmol) and B15 (4.88 g; 10 mmol) are used to replace A1 and B1, respectively, to obtain the product C15: 5.45 g (yield: 81%), MS (m / z) (M+): 673.

[0170] Synthesis Example 16

[0171]

[0172] The method is the same as that of Synthesis Example 1, except that A16 (3.09 g; 10 mmol) and B16 (4.88 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C16: 6.26 g (yield: 93%), MS (m / z) (M+): 673.

[0173] Synthesis Example 17

[0174]

[0175] The method is the same as that of Synthesis Example 1, except that A17 (3.09 g; 10 mmol) and B17 (4.12 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C17: 5.25 g (yield: 88%), MS (m / z) (M+): 597.

[0176] Synthesis Example 18

[0177]

[0178] The method is the same as that of Synthesis Example 1, except that A18 (3.09 g; 10 mmol) and B18 (4.12 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C18: 4.89 g (yield: 82%), MS (m / z) (M+): 597.

[0179] Synthesis Example 19

[0180]

[0181] The method is the same as that of Synthesis Example 1, except that A19 (3.09 g; 10 mmol) and B19 (4.12 g; 10 mmol) are used to replace A1 and B1, respectively, to obtain the product C19: 5.43 g (yield: 91%), MS (m / z) (M+): 597.

[0182] Synthesis Example 20

[0183]

[0184] The method is the same as that of Synthesis Example 1, except that A20 (3.09 g; 10 mmol) and B20 (4.12 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C20: 5.55 g (yield: 93%), MS (m / z) (M+): 597.

[0185] Synthesis Example 21

[0186]

[0187] The method is the same as that of Synthesis Example 1, except that A21 (3.09 g; 10 mmol) and B21 (4.62 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C21: 5.24 g (yield: 81%), MS (m / z) (M+): 647.

[0188] Synthesis Example 22

[0189]

[0190] The method is the same as that of Synthesis Example 1, except that A22 (3.09 g; 10 mmol) and B22 (4.12 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C22: 5.61 g (yield: 94%), MS (m / z) (M+): 597.

[0191] Synthesis Example 23

[0192]

[0193] The method is the same as that of Synthesis Example 1, except that A23 (3.09 g; 10 mmol) and B23 (4.62 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C23: 5.76 g (yield: 89%), MS (m / z) (M+): 647.

[0194] Synthesis Example 24

[0195]

[0196] The method is the same as that of Synthesis Example 1, except that A24 (3.09 g; 10 mmol) and B24 (4.62 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C24: 5.56 g (yield: 86%), MS (m / z) (M+): 647.

[0197] Synthesis Example 25

[0198]

[0199] The method is the same as that of Synthesis Example 1, except that A25 (3.09 g; 10 mmol) and B25 (4.62 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C25: 6.15 g (yield: 95%), MS (m / z) (M+): 647.

[0200] Synthesis Example 26

[0201]

[0202] The method is the same as that of Synthesis Example 1, except that A26 (3.09 g; 10 mmol) and B26 (3.65 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C26: 4.62 g (yield: 84%), MS (m / z) (M+): 550.

[0203] Synthesis Example 27

[0204]

[0205] The method is the same as that of Synthesis Example 1, except that A27 (3.09 g; 10 mmol) and B27 (3.64 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C27: 4.83 g (yield: 88%), MS (m / z) (M+): 549.

[0206] Synthesis Example 28

[0207]

[0208] The method is the same as that of Synthesis Example 1, except that A28 (3.09 g; 10 mmol) and B28 (3.64 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C28: 4.78 g (yield: 87%), MS (m / z) (M+): 549.

[0209] Synthesis Example 29

[0210]

[0211] The method is the same as that of Synthesis Example 1, except that A29 (3.09 g; 10 mmol) and B29 (2.88 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C29: 3.78 g (yield: 80%), MS (m / z) (M+): 473.

[0212] Synthesis Example 30

[0213]

[0214] The method is the same as that of Synthesis Example 1, except that A30 (3.09 g; 10 mmol) and B30 (3.88 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C30: 4.87 g (yield: 85%), MS (m / z) (M+): 573.

[0215] Synthesis Example 31

[0216]

[0217] The method is the same as that of Synthesis Example 1, except that A31 (3.09 g; 10 mmol) and B31 (2.88 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C31: 4.35 g (yield: 92%), MS (m / z) (M+): 473.

[0218] Synthesis Example 32

[0219]

[0220] The method is the same as that of Synthesis Example 1, except that A32 (3.09 g; 10 mmol) and B32 (3.88 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C32: 5.1 g (yield: 89%), MS (m / z) (M+): 573.

[0221] Synthesis Example 33

[0222]

[0223] The method is the same as that of Synthesis Example 1, except that A33 (3.09 g; 10 mmol) and B33 (3.88 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C33: 5.04 g (yield: 88%), MS (m / z) (M+): 573.

[0224] Synthesis Example 34

[0225]

[0226] The method is the same as that of Synthesis Example 1, except that A34 (3.09 g; 10 mmol) and B34 (3.88 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C34: 4.87 g (yield: 85%), MS (m / z) (M+): 573.

[0227] Synthesis Example 35

[0228]

[0229] The method is the same as that of Synthesis Example 1, except that A35 (3.09 g; 10 mmol) and B35 (2.88 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C35: 4.02 g (yield: 85%), MS (m / z) (M+): 473.

[0230] Synthesis Example 36

[0231]

[0232] The method is the same as that of Synthesis Example 1, except that A36 (3.09 g; 10 mmol) and B36 (3.12 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C36: 4.47 g (yield: 90%), MS (m / z) (M+): 497.

[0233] Synthesis Example 37

[0234]

[0235] The method is the same as that of Synthesis Example 1, except that A37 (3.09 g; 10 mmol) and B37 (3.12 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C37: 4.72 g (yield: 95%), MS (m / z) (M+): 497.

[0236] Synthesis Example 38

[0237]

[0238] The method is the same as that of Synthesis Example 1, except that A38 (3.09 g; 10 mmol) and B38 (3.12 g; 10 mmol) are used to replace A1 and B1, respectively, to finally obtain product C38: 4.62 g (yield: 93%), MS (m / z) (M+): 497.

[0239] Comparative Examples 1-4

[0240] Some of the compounds developed in the research have the following structures:

[0241]

[0242] Material performance evaluation

[0243] In order to illustrate the stability of the material of the present invention in terms of ring tension compared with the comparative material, the ring tension is evaluated by calculating the bending angle, which reflects the stability of the chelate. The larger the bending angle, the greater the ring tension and the more unstable the chelate. The calculation formula of the bending angle is as follows:

[0244] Flexion angle = (theoretical bond angle - actual bond angle) / 2;

[0245] Among them, the ring atoms are all SP3 hybridized rings, usually referring to rings without unsaturated bonds, and the theoretical bond angle of the ring is 109°28′. When the ring atoms are SP2 hybridized, it usually refers to a ring containing conjugated double bonds, and the theoretical bond angle of the ring is 120°, such as the bond angle of a benzene ring is 120°; in addition, in order to illustrate that the material of the present invention connects a large planar heteroaryl with quinoline and appropriately adjusts the electron-rich aromatic fragment, so that the structure of the material of the present invention has good rigidity and thus has a large mobility, the present invention uses Gaussian16 software and the B3LYP / 6-31G(d) method to obtain the electronic reorganization energy of the material. The smaller the electronic reorganization energy, the smaller the energy lost in the vibration relaxation of the structure when the material transmits electrons, the faster the electron transmission process, and the larger the corresponding electron mobility. The results are shown in Table 1.

[0246] Table 1 Material performance test results

[0247]

[0248]

[0249] Note: DBCG04 cannot form a chelate ring, so the flexion angle cannot be calculated.

[0250] It can be seen from the above results that the material of the present invention has a smaller bending angle and smaller electron reorganization energy than the comparative material. This is because the present invention uses a chelating quinoline fragment to form a stable six-membered chelate ring, which increases the electron generation and injection capabilities of the material. At the same time, the present invention introduces a rigid heteroaryl group with a larger conjugated surface and is mostly asymmetric in structure, which has a smaller electron reorganization energy. The planar rigid fragment is also conducive to molecular stacking and an increase in mobility, so that the device prepared by the material of the present invention has better device performance.

[0251] Fabrication and characterization of OLEDs

[0252] Device Embodiment

[0253] The organic electroluminescent device provided by the present invention comprises an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer which are sequentially arranged on a substrate;

[0254] Further, the first hole transport region includes a hole injection layer, a first hole transport layer and a first electron blocking layer; the first electron transport region includes a first hole blocking layer and a first electron transport layer; the charge generation region includes an n-type charge generation layer and a p-type charge generation layer; the second hole transport region includes a second hole transport layer and a second electron blocking layer; the second electron transport region includes a second hole blocking layer, a second electron transport layer and an electron injection layer.

[0255] Furthermore, the light-emitting layer is composed of a main material and a doping material, and the main material of the light-emitting layer can be composed of one molecular material or multiple molecular materials.

[0256] The deuterated organic compound of the present invention can be used in one or more layers of the above-mentioned organic electroluminescent device, preferably used as the n-type charge generation layer material of the device.

[0257] The anode in the embodiment adopts anode materials commonly used in the art, such as ITO, Ag or their multilayer structures. The hole injection layer adopts hole injection materials commonly used in the art, and F4TCNQ, HATCN, NDP-9, etc. are added for doping. The hole transport layer adopts hole transport materials commonly used in the art. The light-emitting layer adopts light-emitting materials and doping materials commonly used in the art, for example, it can be composed of a main material and a doping material. The electron transport layer adopts electron transport materials commonly used in the art. The electron injection layer adopts electron injection materials commonly used in the art, such as Liq, LiF, Yb, etc. The n-type charge generation layer material adopts a deuterated organic compound provided by the benzene invention. The cathode adopts materials commonly used in the art, such as metal Al, Ag or metal mixtures (Ag-doped Mg, Ag-doped Ca, etc.).

[0258] The electrode preparation method and the deposition method of each functional layer in this embodiment are conventional methods in the art, such as vacuum thermal evaporation or inkjet printing, etc., which will not be described in detail here. Only some process details and test methods in the preparation process are supplemented as follows:

[0259] Device Example 1

[0260] The substrates used in the present invention were subjected to the following operations: the ITO substrate was patterned so that its luminous area had a size of 3 mm×3 mm, and then ultrasonically treated with water / isopropanol, UV / ozone irradiation, and then dried at 100°C. After that, the ITO substrate was mounted on a substrate holder of a vacuum deposition device and the pressure was adjusted so that the vacuum rate became 1×10 -7 torr.

[0261] Subsequently, HTL-1 and p-dopant-1 (the mass ratio of HTL-1 to p-dopant-1 is 97:3) are vacuum deposited on the ITO layer (anode) formed on the substrate with a thickness of 10 nm to form a hole injection layer; secondly, HTL-1 is vacuum deposited on the hole injection layer with a thickness of 20 nm to form a first hole transport layer; secondly, EB-1 is vacuum deposited on the first hole transport layer with a thickness of 5 nm to form a first electron blocking layer; secondly, a mixture of BH-1 and BD-1 is vacuum deposited on the first electron blocking layer with a thickness of 20 nm to form a first light-emitting layer, wherein BH- 1 as the host and BD-1 as the dopant, the mass ratio of the host to the dopant is 98:2; then on the first light-emitting layer, HB-1 is vacuum deposited with a thickness of 5nm to form a first hole blocking layer; then on the first hole blocking layer, ET-1 and Liq are vacuum deposited with a thickness of 15nm (the mass ratio of ET-1 to Liq is 1:1) to form a first electron transport layer; then on the first electron transport layer, C1 and Yb are vacuum deposited with a thickness of 15nm (the mass ratio of C1 to Yb is 98:2) to form an n-type charge generation layer, and HTL-1 and p-dopant are vacuum deposited with a thickness of 10nm -1 (the mass ratio of HTL-1 to p-dopant-1 is 97:3) to form a p-type charge generation layer, and then on the above-mentioned p-type charge generation layer, HTL-1 is vacuum deposited with a thickness of 20nm to form a second hole transport layer, and then on the above-mentioned second hole transport layer, EB-1 is vacuum deposited with a thickness of 5nm to form a second electron blocking layer, and then on the above-mentioned second electron blocking layer, a mixture of BH-1 and BD-1 is vacuum deposited with a thickness of 20nm to form a second light-emitting layer, wherein BH-1 is used as a host and BD-1 is used as a dopant, and the mass ratio of the host to the dopant is 98:2; then on the above-mentioned second light-emitting layer, a mixture of BH-1 and BD-1 is vacuum deposited with a thickness of 20nm to form a second light-emitting layer. The method comprises the following steps: first, vacuum depositing HB-1 with a thickness of 5 nm on the cathode layer to form a second hole blocking layer; then vacuum depositing ET-1 and Liq (the mass ratio of ET-1 to Liq is 1:1) with a thickness of 15 nm on the second hole blocking layer to form a second electron transport layer; then depositing Yb with a thickness of 1 nm on the second electron transport layer to form an electron injection layer; then depositing Mg and Ag (the mass ratio of Mg to Ag is 1:9) with a thickness of 15 nm on the electron injection layer to form a cathode; and then depositing CPL-1 with a thickness of 50 nm on the cathode to form a covering layer to prepare a stacked organic electroluminescent device.

[0262] In addition to the materials used in the present invention, the molecular structures of the remaining materials in each layer of the device are as follows:

[0263]

[0264] Device Example 2-38

[0265] The above method is used to prepare the compound described in the embodiment into an organic electroluminescent device, wherein C2 to C38 are used to replace C1 to prepare organic electroluminescent device embodiments 2-38.

[0266] Device Comparison Examples 1-4

[0267] The above method was used to prepare the compounds described in the examples into organic electroluminescent devices, wherein DBCG01 to DBCG04 were used to replace C1 to prepare organic electroluminescent device comparative examples 1-4.

[0268] The OLED devices described above were tested by standard methods. For this purpose, at J = 10 mA / cm 2 The driving voltage, brightness, electroluminescent current efficiency (measured in cd / A) and external quantum efficiency (EQE, measured in percentage) of the organic electroluminescent device are determined at a current density of 500 mA / cm2, which is calculated as a function of the luminous density from the current / voltage / luminous density characteristic line (IVL characteristic line) showing Lambertian emission characteristics. The lifetime LT is defined as the time after which the brightness drops from the initial luminous brightness L0 to a specific proportion L1 when operating at a constant current J; J = 50 mA / cm2 2 The expression L1 = 90% means that at 50 mA / cm 2 When working under LT, the luminance drops to 90% of its initial value L0 after time LT. Similarly, J = 20 mA / cm 2 , L1 = 95% means, at 20mA / cm 2 When working under LT, the luminous brightness drops to 95% of its initial value L0 after time LT.

[0269] The data of various OLED devices are summarized in Table 2. Various parameters of the device examples and the device comparative examples are compared to show the performance data of various OLED devices.

[0270] The test instruments and methods for testing the performance of the OLED devices in the above embodiments and comparative examples are as follows:

[0271] Current efficiency CE (cd / A) and color coordinates (CIEy) were tested using a spectrum scanner PhotoResearch PR-635;

[0272] Current density and lighting voltage: tested using a digital source meter Keithley 2400;

[0273] Blue index is obtained by dividing the current efficiency CE (cd / A) by the color coordinate (CIEy);

[0274] Life test: Use F STAR's silicon photoelectric OLED device life test system.

[0275] The performance test results of the above devices are listed in Table 2.

[0276] Table 2 Device performance test results

[0277]

[0278]

[0279] It can be seen from the above device results that the material designed by the present invention has a lower driving voltage, higher efficiency and longer life compared with the comparative example. This is because the quinoline skeleton adopted by the present invention can form a six-membered stable chelate ring, which can improve the stability of the complex, enhance the doping effect, and improve the electron injection ability on the one hand. On the other hand, the better stability of the complex makes it more difficult for metal ions to diffuse, avoiding the material degradation and life reduction caused by the diffusion of metal ions to the hole end. The substitutable conjugated rigid heteroaryl structure introduced into the structure of the present invention makes the material have a smaller electronic reorganization energy, which is beneficial to improve the mobility, so that the electrons in the charge generation layer can be transmitted to the adjacent layer faster, thereby improving the device efficiency.

[0280] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A quinoline derivative, characterized in that The general structural formula of the quinoline derivative is shown in Formula I; AND; II; Among them, Ar1-Ar9 represent hydrogen, Ar 10 It is represented by the group shown in formula II; or Ar1-Ar7, Ar9, Ar 10 represents hydrogen, Ar8 represents a group represented by formula II; or Ar1-Ar5, Ar7-Ar 10 represents hydrogen, Ar6 represents a group represented by formula II; or Ar1-Ar6, Ar8-Ar 10 represents hydrogen, Ar7 represents a group represented by formula II; In formula II, L represents any one of a single bond and a phenylene group; X means O; Y1 and Y2 each independently represent C or N; Ring A and Ring B each independently represent a benzene ring that can be connected in parallel with the structure of Formula II; Ar 11 Represents pyrene.

2. The quinoline derivative according to claim 1, characterized in that The formula II is selected from one of the structures shown below: 。 3. The quinoline derivative according to claim 1, characterized in that The quinoline derivative is selected from one of the following structures: 。 4. An organic electroluminescent device, characterized in that: It includes an anode, a first hole transport region, a first light-emitting layer, a first electron transport region, a charge generation region, a second hole transport region, a second light-emitting layer, a second electron transport region, a cathode, and a covering layer, which are sequentially arranged on a substrate; wherein the charge generation region includes one or more quinoline derivatives as described in any one of claims 1 to 3.

5. The organic electroluminescent device according to claim 4, characterized in that: The charge generation region comprises an n-type charge generation layer and a p-type charge generation layer, wherein the n-type charge generation layer comprises one or more quinoline derivatives according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Quinoline derivative and application thereof

    CN107778309A